Activation of monocytes and cytokine production in patients with peripheral atherosclerosis obliterans - Corrêa, Camila R. [UNESP] (2011)
Background: Arterial peripheral disease is a condition caused by the blocked blood flow resulting from arterial cholesterol deposits within the arms, legs and aorta. Studies have shown that macrophages in atherosclerotic plaque are highly activated, which makes these cells important antigen-presenting cells that develop a specific immune response, in which LDLox is the inducing antigen. As functional changes of cells which participate in the atherogenesis process may occur in the peripheral blood, the objectives of the present study were to evaluate plasma levels of anti-inflammatory and inflammatory cytokines including TNF-, IFN-, interleukin-6 (IL-6), IL-10 and TGF- in patients with peripheral arteriosclerosis obliterans, to assess the monocyte activation level in peripheral blood through the ability of these cells to release hydrogen peroxide (H2O2) and to develop fungicidal activity against Candida albicans (C. albicans) in vitro. Methods. TNF-, IFN-, IL-6, IL-10 and TGF- from plasma of patients were detected by ELISA. Monocyte cultures activated in vitro with TNF-alpha and IFN-gamma were evaluated by fungicidal activity against C. albicans by culture plating and Colony Forming Unit (CFU) recovery, and by H2O2production. Results: Plasma levels of all cytokines were significantly higher in patients compared to those detected in control subjects. Control group monocytes did not release substantial levels of H2O2 in vitro, but these levels were significantly increased after activation with IFN- and TNF-. Monocytes of patients, before and after activation, responded less than those of control subjects. Similar results were found when fungicidal activity was evaluated. The results seen in patients were always significantly smaller than among control subjects. Conclusions:The results revealed an unresponsiveness of patient monocytes in vitro probably due to the high activation process occurring in vivo as corroborated by high plasma cytokine levels. © 2011 Corrêa et al; licensee BioMed Central Ltd.